2009
DOI: 10.1111/j.1365-3113.2008.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and biogeography of Australian rhopalosomatid wasps (Hymenoptera: Rhopalosomatidae) with a global synopsis of the enigmatic genusOlixonCameron

Abstract: The wasp family Rhopalosomatidae is represented in Australia only by the genus Olixon Cameron. Species of this genus have previously been considered rare based on material in collections and have rarely been observed in the field. All known species of Olixon are brachypterous, solitary ectoparasitoids of crickets (Orthoptera: Gryllidae). Prior to our study the world fauna comprised 11 species of which two were endemic to north‐eastern Australia. Based on specimens collected during recent intensive surveys in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Although a species-level identification key for Rhopalosoma exists (Townes 1977), accurate identification remains a challenge. Other genera within Rhopalosomatidae (i.e., Liosphex, Olixon and Paniscomima) have received major taxonomic updates since Townes' family revision in 1977 and many new species have been discovered (e.g., Guidotti 2007;Krogmann et al 2009;Lohrmann and Ohl 2010;Lohrmann 2011;Lohrmann et al 2012). Rhopalosoma, however, has remained almost untouched apart from minor, mostly faunistic notes (e.g., Freytag 1984;Coronado Blanco and Cancino 2002;Smith 2008) with the exception of the description of the first fossil species in the genus (Lohrmann et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a species-level identification key for Rhopalosoma exists (Townes 1977), accurate identification remains a challenge. Other genera within Rhopalosomatidae (i.e., Liosphex, Olixon and Paniscomima) have received major taxonomic updates since Townes' family revision in 1977 and many new species have been discovered (e.g., Guidotti 2007;Krogmann et al 2009;Lohrmann and Ohl 2010;Lohrmann 2011;Lohrmann et al 2012). Rhopalosoma, however, has remained almost untouched apart from minor, mostly faunistic notes (e.g., Freytag 1984;Coronado Blanco and Cancino 2002;Smith 2008) with the exception of the description of the first fossil species in the genus (Lohrmann et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological phylogenies have been reconstructed for the closely related Paniscomima Enderlein (Guidotti 2007), the brachypterous Olixon Cameron (Krogmann et al 2009), and the family as a whole (Guidotti 1999). However, no comprehensive molecular study has focused on the Rhopalosomatidae itself, nor thoroughly examined any individual genus within it.…”
Section: Introductionmentioning
confidence: 99%
“…Rhopalosomatidae Ashmead: Brues, 1922: 102 (and most subsequent authors). Krogmann et al, 2009) Among aculeate Hymenoptera, Rhopalosomatidae can be easily identified by the following combination of characters: basal flagellomeres with distinct apical bristle(s) (Figs. 3a, d, 4d, 5b, 6c-e; very small or completely reduced in many Olixon), mesosternum with posterad paired lobes covering the bases of the mesocoxae (Figs.…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…In Australia, this small family is known from 17 described species that belong to the antlike, wing-reduced genus Olixon (Krogmann et al 2009). These species are distributed throughout the Australian continent, including arid and semi-arid and wet tropical habitats (Krogmann et al 2009). This genus may also occur in New Guinea but the family is absent from New Zealand and New Caledonia.…”
Section: Metaponementioning
confidence: 99%
“…This genus may also occur in New Guinea but the family is absent from New Zealand and New Caledonia. Although no host records are known from Australia, members of this family are all thought to be ectoparasitoids of crickets (Orthoptera: Gryllidae) (Townes 1977a;Krogmann et al 2009).…”
Section: Metaponementioning
confidence: 99%